Atendimento antirrábico humano pós-exposição: proposta de intervenção e estudo da percepção do comportamento de cães e gatos envolvidos nos agravos - Grisólio, Ana Paula Rodomilli [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In Brazil, although urban rabies is controlled in most states, the costs with human post-exposure prophylactic treatment are very high. This concerns particularly the Ministry of Health. Therefore, this study aimed propose strategic measures to improve the medical service to people involved with animals attacks, in Jaboticabal, São Paulo, reducing the number of rabies post-exposure treatments. Were used as tools, two new records, the record of Reference for Animal Aggression and the record of Zoossanitaries Visits. Home visits with the purpose of assisting in investigations of reported cases and analyze the behavior of the animals involved were also performed. Between the months of September 2012 and August 2013, 226 cases of injuries were reported and made 185 visits. The species of greatest interest in aggravations was the canine (86%), followed by feline (11,5%) and other species such as rodents, primates and cattle (2.5%). Dogs and cats observed during the 10 days after the accident, 65,5 % were domiciled, 57,5% vaccinated against rabies and 88% remained healthy until the end of the period. The anatomic areas most affected were hands (40,5%) and lower limbs (34%). In total 316 doses of rabies vaccine were used. Based on the data of the chips and analysis of animal health visits, it was found that 248 vaccines could have been dispensed, which represents a saving of over $3.000,00, only considered the cost immunobiological. If were computed all direct and indirect expenses, this number could triple. The inclusion of content analysis occurred, to interpret the descriptions given by the victims about how the injuries, allowed a more accurate assessment of the circumstances involved and the real reasons that led to aggression by animals. The project involved the public and the employees of the Health Department of the Municipality studied, seeking greater integration of medical and veterinary ...

No Brasil, embora a raiva urbana esteja controlada na maioria dos estados, são elevados os números de tratamentos humanos pós-exposição. Isto preocupa, particularmente, o Ministério da Saúde, devido aos altos custos que essa ação acarreta. Por este motivo, o presente estudo teve como objetivo propor medidas de intervenção para a melhoria do atendimento a pessoas envolvidas em agravos com animais no Município de Jaboticabal, São Paulo, visando a redução do número de tratamentos antirrábicos humanos pós-exposição. Foram propostas, como ferramentas de intervenção no atendimento antirrábico, a ficha de referência de atendimento à agressão animal e a ficha de visita zoossanitária. Também foram realizadas visitas domiciliares com a finalidade de auxiliar nas investigações dos casos notificados e analisar o comportamento dos animais envolvidos. Entre os meses de setembro de 2012 e agosto de 2013, foram notificados 226 casos de agravos e realizadas 185 visitas. A espécie de maior participação nos agravos foi a canina (86%), seguida da felina (11,5%) e de outras espécies, como roedores, primatas e bovino (2,5%). Dos cães e gatos observados durante os 10 dias pós- acidente, 65,5% eram domiciliados, 57,5% vacinados contra a raiva e 88% permaneceram sadios ao final do período. As áreas anatômicas mais afetadas foram as mãos (40,5%) e os membros inferiores (34%). No total foram utilizadas 316 doses de vacina antirrábica. Com base nos dados das fichas e na análise das visitas zoossanitárias, constatou-se que 248 doses poderiam ter sido dispensadas, o que representa uma economia de mais de 3 mil dólares, somente considerado o custo com imunobiológicos no município de estudo; se fossem computados todos os gastos diretos e indiretos, este valor triplicaria. A inclusão da Análise de Conteúdo para interpretar as descrições feitas pelas vítimas sobre como os agravos ...
Keywords: Cão; Gato; Hidrofobia; Zoonose; Animais - Comportamento; Diseases